2020
DOI: 10.1016/j.waojou.2020.100116
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic esophagitis in esophageal atresia: Tertiary care experience of a “selective” approach for biopsy sampling

Abstract: Background: A high prevalence (9.5-30%) of eosinophilic esophagitis (EoE) in patients with esophageal atresia (EA) has been reported. The application of the EoE criteria to EA patients might be problematic. To date, only studies using a "routine" biopsy approach, even in asymptomatic patients, have been performed. The aim of the study was to establish the prevalence of EoE among symptomatic EA patients (EA/EoE group) without anastomotic stricture (AS) and to compare their characteristics with those of EoE pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…Many factors may explain these findings. The literature available on EoE prevalence in EA patients is contradictory: some studies identified a 20% prevalence [13][14][15], similar to the one that we report in the present study, while another recent cohort study detected a lower prevalence of less than 5% [16]. The main factor responsible for this discrepancy may be the different approaches to esophageal sampling: according to the ESPGHAN guidelines, endoscopy with biopsies is mandatory for the routine monitoring of GERD or any type of esophagitis in patients with EA; therefore, while Tambucci et al chose a "selective" approach in symptomatic children, we routinely perform esophageal biopsies during all routine endoscopies of the protocol, i.e., at 6-12 months before stopping PPI therapy and, in the case of asymptomatic patients, at 5, 10 and 15 years [3].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Many factors may explain these findings. The literature available on EoE prevalence in EA patients is contradictory: some studies identified a 20% prevalence [13][14][15], similar to the one that we report in the present study, while another recent cohort study detected a lower prevalence of less than 5% [16]. The main factor responsible for this discrepancy may be the different approaches to esophageal sampling: according to the ESPGHAN guidelines, endoscopy with biopsies is mandatory for the routine monitoring of GERD or any type of esophagitis in patients with EA; therefore, while Tambucci et al chose a "selective" approach in symptomatic children, we routinely perform esophageal biopsies during all routine endoscopies of the protocol, i.e., at 6-12 months before stopping PPI therapy and, in the case of asymptomatic patients, at 5, 10 and 15 years [3].…”
Section: Discussionsupporting
confidence: 84%
“…First, it seems that EA patients may have an earlier onset of EoE than children from the general population; as postulated before, this particular group of patients undergoes routine surveillance endoscopy with adequate biopsy mapping, which might enable the early diagnosis of EoE, even when symptoms are still mild [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include patients previously treated for esophageal atresia and tracheoesophageal fistula (Figure 3 ). Common complications among these patients include esophagitis[ 13 ], recurrent respiratory tract infection, tracheomalacia and poor growth with increased healthcare utilization[ 14 - 16 ]. Pediatric gastroenterology input can be crucial to evaluate for anatomic and mucosal esophageal abnormalities and for persistent tracheoesophageal fistula, which can be difficult to diagnosis.…”
Section: Aerodigestive Program Servicesmentioning
confidence: 99%
“…The estimated prevalence of EoE in EA ranges from 9.5% to 30% thus it is significantly higher than that observed in the general population (0.1%–0.5%) (6–11). Although, there is still an ongoing debate as to whether esophageal eosinophilia in EA patients shares the same pathophysiological mechanisms of EoE in the general population (12,13), current evidence indicates that treatments resulting in mucosal eosinophil count reduction led to a significant improvement of dysphagia and GERD symptoms and lower the occurrence of AS in EA children (8).…”
mentioning
confidence: 99%